2015
DOI: 10.3855/jidc.6336
|View full text |Cite
|
Sign up to set email alerts
|

Inducible and constitutive clindamycin resistance in Staphylococcus aureus in a northeastern Indian tertiary care hospital

Abstract: Introduction: Staphylococcus aureus is one of the most common pyogenic bacteria. They are notorious for developing prompt resistance to newer antimicrobials. With increasing incidence of methicillin-resistant S. aureus (MRSA) isolates, the treatment options are also becoming limited. Clindamycin is an excellent drug for skin and soft tissue infections, but resistance mediated by the inducible phenotype (iMLS B ) leads to in vivo therapeutic failure even though there may be in vitro susceptibility. The double d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 19 publications
3
13
1
Order By: Relevance
“…Truly clindamycinsensitive isolates, which exhibit MS phenotype, were present in 14.38% of MSSA and 9.68% of MRSA isolates in our study. This result is similar to Banik et al, (2015) and Phukan et al, (2015 …”
Section: Resultssupporting
confidence: 88%
“…Truly clindamycinsensitive isolates, which exhibit MS phenotype, were present in 14.38% of MSSA and 9.68% of MRSA isolates in our study. This result is similar to Banik et al, (2015) and Phukan et al, (2015 …”
Section: Resultssupporting
confidence: 88%
“…Perumal et al 5 have reported the bi-functional enzyme aac (6′) Ieaph (2’’) (55.4%) as the predominant AME followed by aph (3’) IIIa (32.3%) and ant (4’) Ia gene (9%). The incidence of inducible (iMLS B ) and constitutive (cMLS B ) clindamycin resistance was higher in MRSA (iMLS B ; 19-28%, cMLS B ; 17-41%) than MSSA (iMLS B ; 6-10 per cent, cMLS B ; 5-10%)6789101112. Inducible clindamycin resistance is conferred through erm A (20%) and erm C (52%) genes3.…”
Section: Gram-positive Organismsmentioning
confidence: 96%
“…In different studies, the inducible clindamycin ranged from 0% to 37.1% [ Table 4 ]. [ 7 12 15 16 17 18 19 20 21 22 23 24 25 26 27 ] It was observed that percentage of inducible clindamycin resistance was higher among MRSA (24.8%) compared to MSSA (7.5%). The difference between MSSA and MRSA isolates were not statistically significant ( P = 0.2340).…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] In different studies, authors have reported the MS phenotype varies between 0.7% and 44.6% [ Table 4 ]. [ 7 12 15 16 17 18 19 20 21 22 23 24 25 26 27 ] This result implies that clindamycin can be safely and effectively instituted as a therapeutic option in this group of patients even in the presence of macrolide resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation